Network Pharmacology Uncovers Anticancer Activity of Mammea-Type Coumarins from Calophyllum brasiliense - Gómez-Verjan, Juan Carlos; Rivero-Segura, Nadia Alejandra; Estrella-Parra, Edgar; Rincón-Heredia, Ruth; Madariaga-Mazón, Abraham; Flores-Soto, Edgar; González-Meljem, Mario; Cerbón, Marco; Reyes-Chilpa, Ricardo (Planta Medica, 2019)
Mammea-type coumarins are a particular type of secondary metabolites biosynthesized by the tropical rainforest tree Calophyllum Brasiliense, which is distributed from South America to Mexico. Particularly, mammea A/BA and A/BB (alone or as a mixture) possess biological properties such as cytotoxic and antitumoral activities, however, most of its molecular targets remain unknown. In this context, novel bioinformatic approaches, such as network pharmacology analysis, have been successfully used in herbal medicine to accelerate research in this field, and the support of experimental validations has been shown to be quite robust. In the present study, we performed a network pharmacology analysis to assess the possible molecular biological networks that interact with mammea A/BA and A/BB. Moreover, we validated the most relevant networks experimentally in vitro on K562 cancer cells. The results of the network pharmacology analysis indicate that mammea A/BA and A/BB interacts with cell death, PI3K/AKT, MAPK, Ras, and cancer pathways. The in vitro model shows that mammea A/BA and A/BB induce apoptosis through the overexpression of the proapoptotic proteins Bax and Bak, disrupt the autophagic flux as seen by the cytosolic accumulation of LC3-II and p62, disrupting the mitochondria ultrastructure and concomitantly increase the intracellular calcium concentration. Additionally, docking analysis predicted a possible interaction with a rapamycin-binding domain of mTOR. In conclusion, we validated network pharmacology analysis and report, for the first time, that mammea A/BA and A/BB coumarins induce apoptosis through the inhibition of the autophagic flux, possibly interacting with mTOR.
Keywords: network pharmacology; anticancer; mammea-type coumarins; Calophyllum brasiliense; cell death; autophagy; Clusiaceae